Meid, V. Das Buch der Literatur. Deutsche Literatur vom frühen Mittelalter bis ins 21. Jahrhundert. Jubiläumsausgabe [2004], Stuttgart, Reclam, 2017, 526 pp. 604 Abb. ISBN: 978-3-15-011117-8. - Ducatteau, Héloïse Elisabeth Marie-Vincent Ghislaine (Magazin, 2022)
book review